Maternal folate depletion during early development and high fat feeding from weaning elicit similar changes in gene expression, but not in DNA methylation, in adult offspring. Issue 4 (6th February 2017) - McKay, Jill A.; Xie, Long; Adriaens, Michiel; Evelo, Chris T.; Ford, Dianne; Mathers, John C.
Abstract : Nutritional factors influence health throughout the life course. Here, we discovered that (i) inadequate intake of the B vitamin folate during pregnancy and lactation and (ii) feeding a high‐fat diet from weaning had very similar effects on gene expression in the liver. These findings suggest that these two diverse nutritional insults influence health through similar molecular mechanisms. Abstract : Scope: The 'Predictive Adaptive Response' hypothesis suggests that the in utero environment when mismatched with the post‐natal environment can influence later life health. Underlying mechanisms are poorly understood, but may involve gene transcription changes regulated via epigenetic mechanisms. Methods and results: In a 2 × 2 factorial design, female C57Bl/6 mice were randomised to low or normal folate diets (0.4 mg/2 mg folic acid/kg diet) prior to and during pregnancy and lactation with offspring randomised to high‐ or low‐fat diets at weaning. Genome‐wide gene expression and promoter DNA methylation were measured using microarrays in adult male livers. Maternal folate depletion and high fat intake post‐weaning influenced gene expression (1859 and 1532 genes, respectively) and promoter DNA methylation (201 and 324 loci, respectively) but changes in expression and methylation were poorly matched for both dietary interventions. Expression of 642 genes was altered in response to both maternal folate depletion and post‐weaning high fat feeding, treatments imposed separately. In addition, there was evidence that the combined dietary insult (i.e. maternal folate depletion followed by high fat post‐weaning) caused the largest expression change for most genes. Conclusion: Our observations align with, and provide evidence in support of, a potential underlying mechanism for the 'Predictive Adaptive Response' hypothesis.